2021
DOI: 10.1097/scs.0000000000007554
|View full text |Cite
|
Sign up to set email alerts
|

Postoperative Clinical Outcomes Using Standard Variables Following Levator-Mullerectomy Advancement Blepharoptosis Surgery

Abstract: The frontalis suspension procedure is a common surgical method for patients with severe blepharoptosis. While frontalis

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 9 publications
0
2
0
Order By: Relevance
“…For example, Leung et al has conducted a multicenter prospective study and evaluated the effect of 2.5% phenylephrine test, amount of the response to the phenylephrine test and excised MMC tissue on the surgical success rate of the MMCR surgery, however, the measurement method was not stated in the paper (18). Similarly, Dryden et al reported the results of the levator-Muller tissue complex resection (the technique described by Morris et al) surgery for ptosis repair by measuring the MRD1 and stated that, in cases who responded to the phenylephrine test can benefit from the 8 mm and 10 mm resection of the levator-Muller tissue complex, however, the authors did not mention about the MRD1 measurement method in the paper (7).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, Leung et al has conducted a multicenter prospective study and evaluated the effect of 2.5% phenylephrine test, amount of the response to the phenylephrine test and excised MMC tissue on the surgical success rate of the MMCR surgery, however, the measurement method was not stated in the paper (18). Similarly, Dryden et al reported the results of the levator-Muller tissue complex resection (the technique described by Morris et al) surgery for ptosis repair by measuring the MRD1 and stated that, in cases who responded to the phenylephrine test can benefit from the 8 mm and 10 mm resection of the levator-Muller tissue complex, however, the authors did not mention about the MRD1 measurement method in the paper (7).…”
Section: Discussionmentioning
confidence: 99%
“…The Muller's muscle conjunctiva resection (MMCR) (posterior approach) surgery is generally used to correct the functional and aesthetical eyelid issues in cases with mild to moderate ptosis (3). In the literature, studies have been conducted to evaluate the factors that could affect the final surgical outcomes following the MMCR surgery and there are studies conducted to evaluate the association between the amount of the excised Muller's muscle conjunctival (MMC) tissue and final eyelid position and a direct association could not be found in these studies (4)(5)(6)(7).…”
Section: Introductionmentioning
confidence: 99%